Exposure to ambient gaseous pollutant and daily hospitalizations for Sjögren’s syndrome in Hefei: A time-series study - Zhang, Tian-Ping; Wang, Li-Jun; Wang, Shan; Wang, Ping; Zhou, Xiao-Hui; Wang, Li; Yang, Chun-Mei; Li, Xiao-Mei (Frontiers in Immunology, 2022)
Objective: Increasing evidence suggested that gaseous pollutants were associated with the development of autoimmune diseases, while there were few studies on the association between gaseous pollutants and Sjögren's syndrome (SS). This study sought to assess the relationship between exposure to several gaseous pollutants and the hospitalizations for SS. Methods: The data regarding SS hospitalizations, gaseous pollutants, and meteorological factors in Hefei from 2016 to 2021 were collected. A distributed lag non-linear model combined with a generalized linear model were adopted to analyze the association between gaseous pollutants and SS hospitalizations, and stratified analyses were also conducted. Results: We detected significant associations between gaseous pollutants (NO2, SO2, O3, CO) and SS hospitalizations. Exposure to NO2 was linked with the elevated risk of hospitalizations for SS (RR=1.026, lag1 day). A positive correlation between CO exposure and hospitalizations for SS was found (RR=1.144, lag2 day). In contrast, exposure to SO2, O3 was respectively related to the decreased risk of hospitalizations for SS (SO2: RR=0.897, lag14 day; O3: RR=0.992, lag9 day). Stratified analyses found that female patients were more vulnerable to these gaseous pollutants. SS patients ≥ 65 years were more susceptible to NO2, CO exposure, and younger patients were more vulnerable to O3 exposure. In addition, exposure to O3, CO in cold season were more likely to affect hospitalizations for SS. Conclusion: Our results demonstrated a significant association between exposure to NO2, CO and elevated risk of hospitalizations for SS, and SO2, O3 exposure might be linked to reduced risk of SS hospitalizations.